Two-column sequential injection chromatography for fast isocratic separation of two analytes of greatly differing chemical properties - Šatínský, Dalibor; Chocholouš, Petr; Válová, Olga; Hanusová, Lucia; Solich, Petr (Talanta, 2013)
This paper deals with a novel approach to separate two analytes with different chemical properties and different lipophilicity. The newly described methodology is based on the two column system that was used for isocratic separation of two analytes with very different lipophilicity-dexamethasone and cinchocaine. Simultaneous separation of model compounds cinchocaine and dexamethasone was carried under the following conditions in two-column sequential injection chromatography system (2-C SIC). A 25×4.6 mm C-18 monolithic column was used in the first dimension for retention and separation of dexamethasone with mobile phase acetonitrile:water 30:70 (v/v), flow rate 0.9 mL min(-1) and consumption of 1.7 mL. A 10×4.6 mm C-18 monolithic column with 5×4.6 mm C-18 precolumn was used in the second dimension for retention and separation of cinchocaine using mobile phase acetonitrile:water 60:40 (v/v), flow rate 0.9 mL min(-1) and consumption 1.5 mL. Whole analysis time including both mobile phase's aspirations and both column separations was performed in less than 4 min. The method was fully validated and used for determination of cinchocaine and dexamethasone in pharmaceutical otic drops. The developed 2-C SIC method was compared with HPLC method under the isocratic conditions of separation on monolithic column (25×4.6 mm C-18). Spectrophotometric detection of both compounds was performed at wavelength 240 nm. System repeatability and method precision were found in the range (0.39-3.12%) for both compounds. Linearity of determination was evaluated in the range 50-500 μg mL(-1) and coefficients of determination were found to be r(2)=0.99912 for dexamethasone and r(2)=0.99969 for cinchocaine.
Keywords: Cinchocaine; Two-column sequential injection chromatography (2-C SIC); anestetika lokální; Sequential injection analysis (SIA); antiflogistika; Pharmaceutical Solutions; Sequential injection chromatography (SIC); lékové roztoky; Dibucaine; Anti-Inflammatory Agents; cinchokain; chromatografie; Anesthetics, Local; Chromatography; dexamethason; Dexamethasone